2009
DOI: 10.1140/epjc/s10052-009-0872-y
|View full text |Cite
|
Sign up to set email alerts
|

Study of B c →J/ψ π, η c π decays with perturbative QCD approach

Abstract: The B c → J/ψπ, η c π decays are studied with the perturbative QCD approach. It is found that the form factors A

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 45 publications
5
48
0
Order By: Relevance
“…[30,31], the harmonic-oscillator wave functions have been applied to describe the charmonium ground state J=ψ, and the theoretical results agree well with the published experimental data. In Ref.…”
Section: Theoretical Frame and The Wave Functionsupporting
confidence: 58%
See 2 more Smart Citations
“…[30,31], the harmonic-oscillator wave functions have been applied to describe the charmonium ground state J=ψ, and the theoretical results agree well with the published experimental data. In Ref.…”
Section: Theoretical Frame and The Wave Functionsupporting
confidence: 58%
“…[33,34], and the wave function of the pseudoscalar meson η c ð2SÞ gets the same access to η c ð1SÞ [30].…”
Section: Theoretical Frame and The Wave Functionmentioning
confidence: 98%
See 1 more Smart Citation
“…The LHCb collaboration has started comprehensive experimental studies of the decays [27], and some phenomenological studies can be found in refs. [28][29][30][31][32].…”
Section: Jhep12(2017)012mentioning
confidence: 99%
“…These methods can be assigned according to the following four types. (i) The perturbative QCD * Electronic address: rlzhu@njnu.edu.cn † Electronic address: xiaozhenjun@njnu.edu.cn (PQCD) approach in which the form factors can be computed in terms of the perturbative hard kernels and the nonperturbative meson wave functions with the harmonic oscillator form [4] or the transverse momentum dependent form [5][6][7].…”
Section: Introductionmentioning
confidence: 99%